Mangroves as "Blue Carbon" resource- a comparative case study of mangrove Ecosystems of Kerala and West Bengal - Suchismita, Saha (KUFOS, 2018)
Abstract- Mangroves are fringe of trees and shrubs that occurs within the littoral zone and muddy shore areas where continuous flush of estuarine or marine waters are felt. Mangrove ecosystem (mainly mangrove sediments) is a blue carbon resource as it is essential in influencing the climate change globally by sequestering carbon dioxide from the atmosphere and oceans at significantly high rates, per unit area than terrestrial forests. When these coastal ecosystems are degraded, lost or converted to other land uses, the large stores of blue carbon in the soils are exposed and released as CO2 into the atmosphere and/or ocean leading to green-house effect and hence, global warming (2-6% of degradation of coastal ecosystems generates 3-19% of carbon emissions). Thus, characterization of organic compounds from mangrove sediment cores (mainly on the parameters- carbohydrates, proteins, lipids, tannin and lignin and TOC) will help in the application in source characterization of organic matter and carbon sequestration capacity of mangroves (blue carbon). A comparative study on the sediments of Kerala (Mangalavanam- Ernakulam and Kollam- Ashramam and Munroe Island regions) and West Bengal (Kaikhali region- Sundarbans) mangrove ecosystems have been carried out in pre-monsoon season (March to May), monsoon season (August and September) and post-monsoon season (November to January) in the year 2017-18 which reveals that mangrove sediments of Kerala have extremely high organic load of labile organic compounds compared to the sediments present in Sundarbans and high tannin and lignin concentration, resulting in severe damage to the bio fauna of Kerala mangroves and simultaneously depicts the upcoming threats of increasing global warming phenomenon in this state in comparison to West Bengal, because these sampling site of mangrove ecosystem in Kerala are in the verge of extinction unlike West Bengal. The destruction of mangrove ecosystem leads to conversion of labileorganic compounds to free carbon dioxide in atmosphere, thus, leading mother earth to stress condition due to increase in the adverse effect of global warming. Humic acids from three different locations of sediments viz, Mangalavanam, Ashramam, and Munroe sediments were isolated and their chemical features were studied using CHNS, UV-Vis, fluorescence, FTIR, 1H NMR. The structural characterization is difficult because of the complexity, but the study could determine mangrove sediment samples contain high levels of phenolic compounds and low level of carboxylic groups in its highly humified, high molecular weight long chain compound.